Financial Access and Household Welfare : Evidence from Mauritania - Amendola, Alessandra (World Bank, Washington, DC, 2016)
This paper evaluates the impact of access to credit from banks and other financial institutions on household welfare in Mauritania. Micro-level data from a 2014 household survey are used to evaluate the relationship between credit access, a range of household characteristics, and welfare indicators. To address potential endogeneity issues, the household isolation level is used to instrument access to credit. The results show that households headed by older, more educated people are more likely to access financial services, as are households located in urban areas. In addition, greater financial access appears to be associated with a reduced dependence on household production and increased investment in human capital.